Nanotechnology-based cosmetics: regulation, claims, and cosmetovigilance - Ajeng Ilillastria Rosalina; Tri Wagiyanti (Sociedade Brasileira de Dermatologia (SBD), 2024)
The rapid expansion of the cosmetics industry has been accompanied by an increasing demand for innovative and customized products based on scientiﬁc base. One of the innovative products is a nanotechnology-based product. This article discusses any potential risks associated with nanotechnology-based cosmetics use, how the government should regulate the product to protect the public and promote public understanding. The government should create effective regulations, but these regulations must not be detrimental to manufacturers. The government has an essential role in establishing effective regulations for both consumers and producers. In addition, the government should encourage manufacturers to provide rational claims and effective advertising.